2022
DOI: 10.1063/5.0087623
|View full text |Cite
|
Sign up to set email alerts
|

Elevated temperature spectroscopic ellipsometry analysis of the dielectric function, exciton, band-to-band transition, and high-frequency dielectric constant properties for single-crystal ZnGa2O4

Abstract: We report the elevated temperature (22 °C [Formula: see text]  T [Formula: see text] 600 °C) dielectric function properties of melt grown single crystal ZnGa2O4 using a spectroscopic ellipsometry approach. A temperature dependent Cauchy dispersion analysis was applied across the transparent spectrum to determine the high-frequency index of refraction yielding a temperature dependent slope of 3.885(2) × 10−5 K−1. A model dielectric function critical point analysis was applied to examine the dielectric function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…However not many studies have discussed these properties for ZnGa 2 O 4 (ZGO) 2 being exposed to high temperatures or the effect of interdiffusion with its substrate. Hilfiker et al have recently reported the dielectric function and interband transitions of melt grown ZGO for temperatures up to 600 • C, where they observed a decrease in bandgap at a slope of − 0.72 meVK − 1 with increasing temperatures [19]. Wang et al studied radio frequency sputtered ZGO thin films on sapphire for temperatures ranging from 500 to 900 • C. They observed an increase in bandgap energy from 4.7 eV to 4.98 eV and improvement in crystal quality with increase in temperature [20].…”
Section: Introductionmentioning
confidence: 99%
“…However not many studies have discussed these properties for ZnGa 2 O 4 (ZGO) 2 being exposed to high temperatures or the effect of interdiffusion with its substrate. Hilfiker et al have recently reported the dielectric function and interband transitions of melt grown ZGO for temperatures up to 600 • C, where they observed a decrease in bandgap at a slope of − 0.72 meVK − 1 with increasing temperatures [19]. Wang et al studied radio frequency sputtered ZGO thin films on sapphire for temperatures ranging from 500 to 900 • C. They observed an increase in bandgap energy from 4.7 eV to 4.98 eV and improvement in crystal quality with increase in temperature [20].…”
Section: Introductionmentioning
confidence: 99%